The Absence of Parents and Psychopathic Disorder in Dismissed Movie - Natania, Hana Kapila (English Department, Faculty of Humanities, Andalas University, 2022)
This study aims to discover the psychopath characteristics of the main character, Lucas, as depicted in the movie Dismissed, and investigate how Lucasâ€™ obsession, which makes him a psychopath, is related to the absence of parents. The qualitative descriptive analysis method is used in analyzing the data. Data is collected by watching, understanding, identifying, interpreting, and analyzing data from the Dismissed movie. Thi study uses psychoanalytic theory by Sigmund Freud and psychopathic personality disorder by Robert D Hare. This study reveals that the absence of parents during Lucasâ€™ developmental period can wreak havoc on the manifestation of psychological disturbance in Lucas. Lucas has a psychopathic personality disorder. His psychopathic problem makes him a killer to gain his excessive obsession to get an â€œAâ€ from his teacher. The writer concludes that Lucasâ€™ psychopathic problem is convincingly connected to parental absence. Lucas experienced imperfect psychosexual development, resulting in fixation at the phallic stage due to the death of his mother and the lack of intense bonding between Lucas and his father as his role model. Lucas becomes a person who has an excessive obsession, has poor behavior control, has no empathy, and has no remorse and guilt. When dealing with trauma and anxiety, Lucasâ€™ ego uses projection as a defense mechanism. He projects the longingness for his mother figure to other women he kills. Therefore, his psychopathic behavior is a means he does to substitute and reduce the anxiety and trauma of parental absence in his life.